Research of influencing factors on permeability for carbonate rocks based on LBM simulation: A case study of low-permeability gas reservoir of Sinian Dengying Formation in Sichuan Basin - Yang, Shan; Yang, Hongzhi; Peng, Xian; Lan, Xuemei; Yang, Yongfei; Zhao, Yi; Zhang, Kai; Chen, Hongde (Frontiers in Earth Science, 2023)
Due to the declining production rate of conventional natural gas reservoir and the rising demand for natural gas resources, conventional natural gas resources cannot satisfy the needs of economic development. Unconventional gas resource is considered to be the most promising energy supplement, therefore it is an inevitable trend to explore and develop unconventional oil and gas resources such as low permeability reservoirs. At present, the carbonate gas reservoirs in the high permeability area in the old area of Sichuan Basin have been almost fully developed, while the remaining gas reservoirs in the low permeability area are not well developed. However, the key factors for effectively enhancing gas recovery rate in different types of low permeability reservoirs are not the same. Even gas reservoirs with the same macroscopic geological characteristics will show different development characteristics through the production processes. In order to analyze the factors affecting the effective production rate of low-permeability gas reservoirs, it is necessary to conduct research from the microscopic perspective, to reveal the effective production conditions of natural gas in low-permeability reservoirs. In this study, low-permeability carbonate samples of Sinian Dengying Formation from Sichuan Basin were taken. Micro-CT scanning technology was used to obtain core images for the carbonate rocks, and the digital carbonate core models at microscopic scale were reconstructed. Based on the reconstructed carbonate digital core models, LBM method was applied to obtain the absolute permeability of the core models. The results imply that the porosity, pore area fraction, throat area fraction, mean throat length, shape factor, coordination number and tortuosity are the factors affecting the absolute permeability of carbonate rocks. Subsequently, the relationship between different pore structure parameters and absolute permeability was obtained by multi-parameter fitting method, which provided a new research method for directly predicting the absolute permeability of carbonate rocks by using pore structure parameters.